Editorial for Special Issue: “Thin Films Based on Nanocomposites (2nd Edition)” - Marcela Socol; Nicoleta Preda (Nanomaterials)
The continuous demand for multifunctional materials in industrial applications has driven the design of nanocomposites with new or enhanced properties [...]